ABSOLUTE GROWTH AND BIOMASS OF Gracilaria sp. THAT CULTIVATED UNDER DIFFERENT DEPTHS - Nurlaila Ervina Herliany; Z Zamdial; Rahma Febriyanti (Jurnal Kelautan, 2017)
There is significant increasing of seaweeds demand over the years that affect the development of seaweeds farming in Indonesia. Gracilaria sp. is one of the species that cultivated in Indonesia. There are some factors that affect the successful of seaweeds cultivation, one of them is cultivation depth. The research was carried out to study the effect of different depth on absolute growth and biomass of Gracilaria sp. Gracilaria sp. was cultivated under three different depths (30, 45 and 60 cm). The result shows that absolute growth and biomass were influenced by cultivation depth. The best treatment was cultivation at 30 cm of depth. Water quality measurements shows that research location is suitable for the growth of seaweeds.Keywords : Absolute growth, Biomass, Cultivation depths, Gracilaria sp